ANALISIS KESALAHAN GURATAN DAN URUTAN PENULISAN MANDARIN PADA SISWA KELAS X1 SMA DARUL ULUM - Sari, Dessy Triana; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractMandarin characters are the smallest scripts used in Chinese writing .In order to write Mandarin characters well, students must learn the basics of writing and sequence of script writing in mandarin. The author after an interview with a teacher at Darul Ulum secondary school, know that many students in the school wrote that the Chinese characters are not good. Therefore the purpose of this study is to know stroke error and sequence of Chinese writing in class XI IPS and XI IPA. According to the author's research also, found that in students XI IPS and XI IPA in the statistical level of stroke writing and sequence of Chinese script writing: more that,espiceally at 2 words?mi,hen?, very many students are wrong in writing strokes and sequence of writing Mandarin characters 90%.Keywords: Mandarin characters,Strokes, Sequence